2017
DOI: 10.1017/s1047951117002050
|View full text |Cite
|
Sign up to set email alerts
|

Late management of truncus arteriosus: 20 years of humanitarian experience

Abstract: Late management and surgery of common arterial trunk is possible with good long-term results without prior hemodynamic examination up to an advanced childhood when signs of left-to-right shunt persist. A high saturation level (above 88%) seems to be a good operability criterion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…30% of patients had significant post-operative pulmonary hypertension with one early mortality (3%) and one late mortality (3%) 6 months post-repair. 18 In our study, 16 patients with late truncus arteriosus presentation underwent surgery at mean age of 5 months, 11(69%) of patients had significant pulmonary hypertension while no patients died within 30 days post-surgery. However, late mortality happened in 25% of patients due to unresolved pulmonary hypertension.…”
mentioning
confidence: 59%
“…30% of patients had significant post-operative pulmonary hypertension with one early mortality (3%) and one late mortality (3%) 6 months post-repair. 18 In our study, 16 patients with late truncus arteriosus presentation underwent surgery at mean age of 5 months, 11(69%) of patients had significant pulmonary hypertension while no patients died within 30 days post-surgery. However, late mortality happened in 25% of patients due to unresolved pulmonary hypertension.…”
mentioning
confidence: 59%
“…In total, 34 articles were assigned to more than one category [ 10–43 ]. The most common category was short-term surgical trip [ 13 , 18 , 20 , 25–50 ] (29 articles, 46%) followed by NGO partnership [ 10 , 11 , 13 , 19–24 , 26–30 , 32–34 , 36–43 , 51–53 ] (28 articles, 44%). Within the short-term surgical trip category, trips ranged from three days to three months, with ten days and two weeks being the most common lengths.…”
Section: Resultsmentioning
confidence: 99%
“…For these articles, post-op follow-up and patient outcomes were deemed not applicable [ 10 , 11 , 13 , 14 , 16 , 45 , 54–56 , 60 , 61 , 64 , 66–68 ]. In the remaining 48 articles, 21 (45%) included post-op follow-up care [ 12 , 15 , 17 , 18 , 20–23 , 27 , 30 , 32 , 33 , 35 , 41 , 42 , 44 , 49 , 53 , 58 , 70 , 71 ] and 31 (66%) included post-op patient outcomes [ 15 , 17 , 18 , 20–23 , 27 , 28 , 30–36 , 39 , 41 , 42 , 44 , 46 , 49 , 51–53 , 58 , 59 , 65 , 69–71 ]. The most reported outcomes were mortality (22/31 articles, 71%) and post-op complications (17/31 articles, 55%) (for a list of outcomes reported, see Table A4 ).…”
Section: Resultsmentioning
confidence: 99%
“…A prior report, describing the outcomes of late referred truncus arteriosus patients, indicated significant pulmonary hypertension requiring specific treatment in 30% of patients (at a mean of three years of age at referral). 12 The same report also suggested that a preoperative oxygen saturation of at least 88% was favorable for complete repair. Pediatric cardiac centers in the developed world typically have the resources to diagnose and manage these patients.…”
Section: Commentmentioning
confidence: 92%